Production and chemical composition of the common black oats fertilized with growing doses of liquid swine manure - Mondardo, Daniela (2011)
The work has as objective evaluate the effect of application of increasing doses of pig slurry under yield and chemical composition of black oat shoot. The experiment was carried out in no-tillage system under experimental design of randomized blocks with four replications and the treatments composed by application of 0; 10; 20; 30; 40; 50 m3 ha-1 of pig slurry. Were determined the yield of total dry mass, the leaf-stem ratio and content of crude protein (CP), acid detergent fiber (ADF), neutral detergent fiber (NDF), mineral matter (MM), organic matter (OM), nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), copper (Cu), zinc (Zn), manganese (Mn), iron (Fe). The application of pig slurry did not promote significant effects on dry mass yield and content of NDF, MM and OM, but promoted linear increase of leaf-stem ratio and of CP and linear decrease in content of ADF. Regarding to minerals, the doses of pig slurry promoted linear increase in contents of N, P, K, Ca, and Zn, without effects on the other studied minerals. The use of pig slurry fertilization on the oat crop until the dose 50 m3 ha-1 does not increase forage production but increases the nutritional value